Pentecost 3 - Achtemeier, Paul J. (Philadelphia : Fortress Press, 1986)
Vol. discusses appointed lessons for the 20th through the last Sundays after Pentecost.
Keywords: Bible -- Homiletical use; Bible -- Liturgical lessons, English; Pentecost season -- Sermons -- Outlines, syllabi, etc